What Drives Human-Centered Leadership? Personal Excellence and Collaborative Excellence with AI Usage - Muhammad Rakha Ardizza; Revin Davian Rangkuti; Maria Grace Herlina (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
Human-centered leadership has become a term established due to increasing concern on organizations that need to balance technological improvement while maintain the importance of human values. This study investigates whether religiosity may serve as a source that is being mediated through personal excellence and collaborative excellence with AI usage as moderating variable. Data were collected from 400 employees across organizational levels in Indonesia, data were analyzed using PLS-SEM through SmartPLS 4.0. The result of this study shows that Religiosity positively strengthens both Personal Excellence (PE) and Collaborative Excellence (CE), which each contribute significantly to the establishment of Human-Centered Leadership (HCL). PE and CE also becomes mediators in this study, meaning that religiosity operates through how individuals develop and express excellence rather than acting on leadership directly. However, AI usage moderated none of these paths. The relationship between excellence and Human-Centered Leadership remains regardless of AI integration level. It provides important insight that AI influence operational efficiency rather than humanistic leadership qualities. These findings also shows that spiritual values may influence the personal and relational excellence that Human-Centered Leadership demands. AI functions as an operational tool, not a substitute of its human factor.